Optical fiber temperature sensor with insensitive refractive index and strain based on phase demodulation. Issue 12 (6th August 2020) - Nan, Tong; Liu, Bo; Wu, Yongfeng; Wang, Junfeng; Mao, Yaya; Zhao, Lilong; Sun, Tingting; Wang, Jin
Abstract: We propose and experimentally demonstrate a temperature sensor based on a suspended‐core microstructure optical fiber (SCMF). The sensor is constructed by fusion splicing a piece of SCMF between two up‐tapers which act as light beam couplers. The Mach‐Zehnder interference (MZI) is formed by the silica core modes and the air cladding modes in the SCMF. The sensitivity of −0.011 rad/°C in the temperature range of 20°C to 90°C is achieved, which is more accurate and stable than conventional wavelength tracking method due to the phase demodulation method can avoid the effects of spectral noise, dip selection, and wavelength sampling rate on the wavelength tracking. In addition, our proposed sensor is inert to external environments such as strain and refractive index, which can well solve the problem of crosstalk during temperature sensing.